2015
DOI: 10.1016/j.coastaleng.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Spectral wave-driven sediment transport across a fringing reef

Abstract: a b s t r a c tA laboratory experiment was conducted to investigate the dynamics of cross-shore sediment transport across a fringing coral reef. The aim was to quantify how a highly bimodal spectrum of high-frequency (sea-swell) and low-frequency (infragravity and seiching) waves that is typically present on coral reef flats, influences the various sediment transport mechanisms. The experiments were conducted in a 55 m wave flume, using a 1:15 scale fringing reef model that had a 1:5 forereef slope, a 14 m lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 60 publications
4
41
0
1
Order By: Relevance
“…First, long wave motions propagating across reef surfaces provide important controls on current and circulation processes across platforms. Second, velocities associated with these wave types are sufficient to entrain and transport detrital sand‐size materials on reef surfaces and govern vectors of sediment transport (e.g., Pomeroy et al, ). Third, results also confirm the importance of long period wave motions as primary processes on reef surfaces that control island inundation at contemporary sea levels (e.g., Beetham et al, ; Cheriton et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, long wave motions propagating across reef surfaces provide important controls on current and circulation processes across platforms. Second, velocities associated with these wave types are sufficient to entrain and transport detrital sand‐size materials on reef surfaces and govern vectors of sediment transport (e.g., Pomeroy et al, ). Third, results also confirm the importance of long period wave motions as primary processes on reef surfaces that control island inundation at contemporary sea levels (e.g., Beetham et al, ; Cheriton et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In between the tidal water fluctuations operating on a time scale of hours and incident waves at time scales of s, infragravity (IG) waves or long waves, which represent water fluctuations on a time scale of 30 s to 5 min, are also of importance. Following early work by Hardy and Young () and Lugo‐Fernandez et al (), the role of IG waves, henceforth IG waves, to reef platform water‐level dynamics has recently been explored in a number of field investigations (Beetham et al, ; Ford et al, ; Péquignet et al, ), laboratory experiments, and numerical modeling (Ma et al, ; Nwogu & Demirbilek, ; Pomeroy et al, ; Shimozono et al, ; Torres‐Freyermuth et al, ; van Dongeren et al, ; Yao et al, ). In particular, the field studies of Péquignet et al () and Pomeroy et al () have shown that incident waves and mean nearshore currents accounted for only a small part of the total observed surface elevation and flow variance in the region between the reef crest and the shoreline of two fringing reefs.…”
Section: Introductionmentioning
confidence: 99%
“…, Dean and Dalrymple , ]. Wave skewness, Sk , and asymmetry, As , were calculated using the third‐order moments of h [ Grasso et al ., ; Pomeroy et al ., ], Sk=true〈trueh3true〉true〈trueh2true〉32 As=false〈scriptH3true(truehtrue)false〉false〈trueh2false〉32 where H is the Hilbert transform and the “∼” indicates the deviation from the burst mean.…”
Section: Methodsmentioning
confidence: 99%
“…This skewness and asymmetry of low‐frequency waves likely contributes to cross‐shore transport of sediment and other material, as was demonstrated in a recent laboratory experiment by Pomeroy et al . []. During large storms and wave events, this transport may be a key determinant of subsequent shoreline erosion or accretion, as has been observed for planar beach coastlines [ Aagaard and Greenwood , ].…”
Section: Introductionmentioning
confidence: 97%
“…Thotagamuwage and Pattiaratchi, 2014a]. These sea-level oscillations play a significant role in a great variety of nearshore processes, such as: wave run-up [Gent, 2001], overwash [McCall et al, 2010], estuarine currents [Uncles et al, 2014], sediment transport [Jannat and Asano, 2007;Pomeroy et al, 2015] or beach morphodynamics [Baldock et al, 2010]. In addition, since they can induce large movements in vessels at port basins during resonant episodes, infragravity waves are of great relevance for port management [e.g.…”
Section: Introductionmentioning
confidence: 99%